2009
DOI: 10.1002/pdi.1324
|View full text |Cite
|
Sign up to set email alerts
|

Embedding CSII therapy in the routine management of diabetes in children: a clinical audit of this service in Leeds

Abstract: The aim of this study was to document the clinical and secondary care cost benefit of continuous subcutaneous insulin infusion (CSII) over a five‐year period in the Leeds Paediatric Diabetes Service. Patients with type 1 diabetes treated using CSII therapy since 2002 who attended the paediatric diabetes clinics in Leeds, UK, were eligible for inclusion. Information on glycaemic control (HbA1c) and frequency/type of hospital admission was collected during the 12‐month period before CSII was initiated and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
11

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 23 publications
1
3
0
11
Order By: Relevance
“…In the present study we observed a greater HbA 1c reduction within 1 year of CSII therapy compared with our previous study [11]. Other studies have also shown short-term improvements in glycaemic control, particularly within the first year of CSII [4,7,[17][18][19].…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…In the present study we observed a greater HbA 1c reduction within 1 year of CSII therapy compared with our previous study [11]. Other studies have also shown short-term improvements in glycaemic control, particularly within the first year of CSII [4,7,[17][18][19].…”
Section: Discussionsupporting
confidence: 60%
“…In the present study, we found that severe hypoglycaemia incidence did not change and DKA increased with CSII therapy. The median (range) pre-CSII start follow-up period (time between earliest recorded HbA 1c to CSII start date) was shorter than the follow-up period after CSII initiation [0.8 (0.01-2) years vs 2.3 (0.1-8.1) years], which may indicate that there was less opportunity for a hospitalization pre-CSII start; however, when comparing pre-CSII start incidence rates between the two studies, severe hypoglycaemia admissions decreased eightfold (8.8 per 100 person-years in the previous study [11] to 1.1 per 100 person-years in the present study) and DKA decreased nearly fourfold (7.6 per 100 person-years in the previous study [11] to 2.2 per 100 person-years), whilst during-CSII incidence rates remained similar. This may reflect improved MDI treatment within the LCYPDS; however, it is disappointing that improvements have not been matched with CSII therapy.…”
Section: Hospitalizationsmentioning
confidence: 76%
See 1 more Smart Citation
“…However, results are inconsistent in children. Only one randomised controlled trial has shown benefit, although many observational studies have demonstrated improved glycaemic control 2 3. Unfortunately, many of these studies are of limited duration.…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, outros dois artigos descreveram que tais episódios podem ocorrer mesmo em uso do SICI (60,65). De acordo com alguns estudos, as hiperglicemias apresentam diferentes causas, como bloqueio da infusão de insulina por desalojamento da cânula (59,60,95,103,105,(118)(119)(120); programações incorretas das taxas basais ou não administração dos bolus (60); término da quantidade de insulina no reservatório (60); descarregamento da bateria ( 60); e oclusão de sistema (68,103,(120)(121)(122)(123). Segundo as evidências apresentadas nos estudos, as causas para oclusão de sistema podem envolver: falta de troca do conjunto de infusão conforme as recomendações; dobra da extensão do sistema de infusão; sangue ou ar no conjunto de infusão; irritação dermatológica no local de inserção (58,60,(126)(127)(128)61,62,65,95,105,118,124,125); insulina turva ( 60); e exposição da insulina em extremos de temperatura (60).…”
Section: Poucos Testes Glicêmicos Capilares Por Dia E Baixo Letramento Em Saúdeunclassified